Laboratory study on the influencing factors and their control for the coefficient of restitution during rockfall impacts - Ji, Zhong-Min; Chen, Zhi-Jian; Niu, Qing-He; Wang, Tian-Jun; Song, Hao; Wang, Ting-Hui (Landslides, 2019)
Different opinions exist in the current research on the COR (coefficient of restitution) of rockfall, and these controversies can be attributed to the difference in the reduction degree of the real impact process during research on rockfall disasters. According to the previous research results, six main controlling factors affecting the COR were comprehensively determined. In this paper, experiments about the effects of the main controlling factors on the COR were conducted; a specially designed rockfall ejector was able to simulate the real rockfall impact process, from which the correlations between the main controlling factors and COR were obtained and then validated by theoretical derivation. By means of the proposed deviation theory between the impact contact point and the projection of mass center, the effects of the block shape on COR values were reasonably explicated. Synthetically, considering the relationships between the characteristic index of surface area distribution and the geometry with normal COR ( R n ), a new index for quantifying the block shape, i.e., shape factor , was introduced, which shows a significant linear correlation of classification with R n . Not equated to IH (inclined impact on a horizontal slope) or II (inclined impact on an inclined slope) in impact experiments of rockfall, the COR values of VI (vertical impact on an incline slope) and its evolving trend with impact angle are varied. COR values are not linearly related to the impact angle completely; kinematic COR ( R v ), tangential COR ( R t ), and R n decrease with the increase of the impact angle and exhibit the power functions. The rotational speed ( ω ) of the block linearly increases with the increase of R t ; the effects of ω and shape on R n are concomitant, and the ω of the non-round-shaped block is not always positively correlated with R n , which may be the opposite when ω is small. The bouncing process is synthetically controlled by multiple influencing factors, and this research will provide an essential foundation for the follow-up study on the COR affected by multiple factors of interaction.